(untitled) (KASBIT Business Journal, 2021)
Trust and perceived risk are found to be substantial in online shopping. But, in the context of social commerce, these are even more imperative because of the prominent role of user generated content in the consumer’s intention to purchase. Hence, this study proposed a double mediation model and examine the effects of trust and perceived risk on intention of consumer to purchase, and the mediating role of seeking of information in social commerce in these relationships. Furthermore, the mediating role of familiarity has also been assessed in the connection amid seeking of information in social commerce and intention of consumer to purchase. Data was collected from 298 respondents living in the city Karachi, Lahore, Islamabad, and Rawalpindi. Smart PLS was used to conduct the data analysis the research suggested that Trust plays a substantial role in stimulating intention of consumer to purchase in the context of social commerce, while seeking of information in social commerce and familiarity both have significant mediating effects in the construct. It is anticipated that the research will serve as a yardstick for the marketing practitioners in designing social commerce strategies focused on enhancing consumer’s online purchase intention.